Pengaturan Pemanfaatan Ruang di Atas Tanah dalam Penerapan Kadaster 3-Dimens - S Hendriatiningsih; Bambang Edhi Leksono; Wisang Wisudanar (Indonesian Journal of Geospatial, 2012)
Abstract. Increasing activity at the infrastructure construction in urban areas causes a revolution in the infrascructure become vertically oriented, means using the space either above or under the land surface. Law Number 16 Year 1985 about Stack Houses have given the arrangement about land registration based on space. This arrangement only to regulate use of space vertically, which the space has land rights and become unseparated part from its building. Therefore, it's necessary to have a regulation about use of the space above the ground which has nothing related with its land rights and basically it's about authorization of space based on volume, therefore it is necessary to apply cadastre 3D concept in its regulation. The study case in this research is Beringhajo Market (Pasar Beringhajo) building which is located on Pabringan Street. The data that are collected consist of physical and juridical data. The 3D cadastre that applied is using Full 3D Cadastre Alternative Combined 2D/3D method as the most accurate method for regulating use of space above the land surface. This method is also used as reference for designing the form of rights and spatial data for use of space above the land surface. The rights form is a product from processing physical and juridical data, while spatial data form is only from physical data processing. From this form designing, a new rights institution which is called rights for using space above the land surface (Hak Guna Ruang di Atas Tanah/HGRAT), and spatial data in volumetric land which is formed in 2.5D registration map and document of measurement certificate, was formed. Keywords : 3D cadastre, use of space above the land surface.